Respuesta :

Answer:

Answer in above picture or attachment

Ver imagen Maheshbabu

Step-by-step explanation:

We can solve this simultaneous equations by using the substitution method.

Equation 1:

[tex] - 2x + 3y = - 3[/tex]

Subtract 3y from both sides.

[tex] - 2x = - 3 - 3y[/tex]

Substitute that new equation into the second equation which is

[tex] - 2x - 5y = - 75[/tex]

to get

[tex] - 3 - 3y - 5y = - 75[/tex]

Simplify:

[tex] - 3 - 8y = - 75[/tex]

Add 3 to both sides:

[tex] - 8y = - 72[/tex]

Divide both sides by -8:

[tex]y = 9[/tex]

To solve for x, simply substitute y=9 into the first equation which is:

[tex] - 2x + 3y = - 3[/tex]

to get

[tex] - 2x + 3(9) = - 3[/tex]

[tex] - 2x + 27 = - 3[/tex]

Subtract 27 from both sides:

[tex] - 2x = - 30[/tex]

Hence,

[tex]x = 15[/tex]

and

[tex]y = 9[/tex]

ACCESS MORE